2020
DOI: 10.1111/mmi.14519
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of protein homeostasis mediates the interaction of Pseudomonas aeruginosa with Staphylococcus aureus

Abstract: In nature, bacteria rarely live in isolation; instead, they form complex multicellular communities where the interactions between different species have an important role in shaping the overall behavior of the microbial community, resulting in many new physiological functions that cannot be achieved by individual constituents (Keller and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 88 publications
3
15
0
Order By: Relevance
“…Although the ClpXP protease has been suggested as a pharmaceutical target (Moreno-Cinos et al, 2019) and anti-virulence drug (McGillivray et al, 2012) to specifically target S. aureus during Pa-Sa co-culture (Yang et al, 2020), it remains questionable whether this is a feasible approach. The recent discovery that ClpXP inactivation increased virulence in P. aeruginosa (Yang et al, 2020) is of specific concern, especially in complex infections that are often polymicrobial. developed an in vitro dual species co-culture system of P. aeruginosa and S. aureus on monolayers of human…”
Section: Molecul Ar Inter Ac Ti On S Of P Aerug Inosa-s Aureus In Co -Culture Smentioning
confidence: 99%
See 3 more Smart Citations
“…Although the ClpXP protease has been suggested as a pharmaceutical target (Moreno-Cinos et al, 2019) and anti-virulence drug (McGillivray et al, 2012) to specifically target S. aureus during Pa-Sa co-culture (Yang et al, 2020), it remains questionable whether this is a feasible approach. The recent discovery that ClpXP inactivation increased virulence in P. aeruginosa (Yang et al, 2020) is of specific concern, especially in complex infections that are often polymicrobial. developed an in vitro dual species co-culture system of P. aeruginosa and S. aureus on monolayers of human…”
Section: Molecul Ar Inter Ac Ti On S Of P Aerug Inosa-s Aureus In Co -Culture Smentioning
confidence: 99%
“…P. aeruginosa also produces pyocyanin that inhibits S. aureus oxidative respiration, the LasA protease that lyses S. aureus cells, and Cis‐2‐decenoic acid and rhamnolipids which promote biofilm dispersal of S. aureus (Hotterbeekx et al., 2017). S. aureus is at an even further disadvantage as it increases P. aeruginosa virulence through the release of the peptidoglycan component N‐acetyl glucosamine (GlcNAc) upon cell lysis or cell wall turnover during growth (Korgaonkar et al., 2013; Yang et al., 2020). Yang et al (2020) recently showed that GlcNAc was important for proteolytic activity in P. aeruginosa, and co‐culture with S. aureus or addition of GlcNAc decreased the activity of the P. aeruginosa caseinolytic protease ClpXP.…”
Section: Molecular Interactions Of P Aeruginosa‐s Aureus In Co‐culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…The Western blot analysis were performed as described previously with some modifications [42][43][44]. Generally, to examine the production of fusion proteins (i.e., p-PhoB-Flag, p-(D)-PhoB-Flag) in P. aeruginosa, overnight LPM cultures of the indicated strains were diluted to OD 600 ≈ 0.05 with fresh LPM medium.…”
Section: Western Blot Analysismentioning
confidence: 99%